2013
DOI: 10.1097/jac.0b013e3182a3e76d
|View full text |Cite
|
Sign up to set email alerts
|

Turning Patient-Centeredness From Ideal to Real

Abstract: The Institute of Medicine's 2001 Crossing the Quality Chasm report established patient-centeredness as 1 of 6 core principles for health system redesign. Yet, turning aspiration into accomplishment has proven arduous. Patient-centered care has components that challenge established professional norms, and the term itself has not always been clearly defined. However, these barriers can be overcome using Rogers' principles of diffusion of innovation, as is shown by 2 case histories. One involves care at an urban … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Co-design and delivery of practitioner training on supporting people with CKD in self-management Marshall and Nelson [13]CF Foundation QI, launched in 2002Patient/family advisory boards at CF care centers, patients/families on clinical practice guidelines committees. Provide input on improvement opportunities“Enriched the improvement work and motivated the clinicians.” Patients and families received center-level access to outcome measures because “it became clear that it was the right thing to do and it would likely help us accelerate improvement” Millenson et al [34]Mercy Clinic, US; also describes University of Pittsburgh Medical Center’s Patient- and Family-Centered Care [23]Patient Advisory Workgroups on Quality at every clinic location. Patients comment on ongoing improvement plans.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-design and delivery of practitioner training on supporting people with CKD in self-management Marshall and Nelson [13]CF Foundation QI, launched in 2002Patient/family advisory boards at CF care centers, patients/families on clinical practice guidelines committees. Provide input on improvement opportunities“Enriched the improvement work and motivated the clinicians.” Patients and families received center-level access to outcome measures because “it became clear that it was the right thing to do and it would likely help us accelerate improvement” Millenson et al [34]Mercy Clinic, US; also describes University of Pittsburgh Medical Center’s Patient- and Family-Centered Care [23]Patient Advisory Workgroups on Quality at every clinic location. Patients comment on ongoing improvement plans.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to improving organizational processes, several articles said patient partnerships benefited patients directly by encouraging deeper communication with providers and motivating improvement and management of personal health [14, 15, 31]. No study reported changes in clinical outcomes associated with engaging patient partners, although three [17, 33, 34] reported correlation with improvements in quality-of-care process measures, including health coaching and care coordination.…”
Section: Resultsmentioning
confidence: 99%
“…Combining TDABC + PFCC M/P proved to be an effective means of identifying the major cost drivers, capacity utilization, areas of opportunity for improving efficiencies, and experiences for this patient population, and all of the information required to participate successfully in bundling and RBP programs for THR and TKR. While the PFCC M/P has already been shown to improve value in health care [4][5][6][7][8][9][10][11], knowing the major cost drivers over a full cycle of care and having the tools to drive down these costs while protecting outcomes and experiences provides the mechanism to further improve value in health care. We are now beginning to build teams to pilot and operationalize identified improvement opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…Identifying the current state of a care experience through the PFCC M/P approach involves process mapping (which in PFCC terms is called Care Experience Flow Mapping) using a tool called Shadowing, which is the real-time observation of patients and families through each segment of their health care journey. The PFCC M/P has been found to improve all three components of value in health care -experience, outcomes, and costs [4][5][6][7][8][9][10][11] -what we call the PFCC Trifecta.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation